2014
DOI: 10.1007/s00726-014-1829-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro evaluation of thiododecaborated α, α- cycloalkylamino acids for the treatment of malignant brain tumors by boron neutron capture therapy

Abstract: Boron-neutron capture therapy (BNCT) is an attractive technique for cancer treatment. As such, α, α-cycloalkyl amino acids containing thiododecaborate ([B12H11](2-)-S-) units were designed and synthesized as novel boron delivery agents for BNCT. In the present study, new thiododecaborate α, α-cycloalkyl amino acids were synthesized, and biological evaluation of the boron compounds as boron carrier for BNCT was carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…The results showed that our compounds exerted selective target in breast cancer cell lines, while they showed no toxic effect against normal cell models. In addition, cellular cytotoxicity is also possibly mediated through the increase of uptake in the cancer cells (Hattori et al, 2014;Miyahara et al, 1993). Hence, the cellular uptake assay for micro-distribution of drug in cells need to be carried out in next studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that our compounds exerted selective target in breast cancer cell lines, while they showed no toxic effect against normal cell models. In addition, cellular cytotoxicity is also possibly mediated through the increase of uptake in the cancer cells (Hattori et al, 2014;Miyahara et al, 1993). Hence, the cellular uptake assay for micro-distribution of drug in cells need to be carried out in next studies.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of KA-BSH was assayed using the water soluble tetrazolium (WST)-8 assay with a cell-counting kit (Wako Pure Chemicals, Osaka, Japan) following a modified version of the manufacturer-provided protocols [ 20 ]. Relative cell survival was calculated according to Equation (1): …”
Section: Methodsmentioning
confidence: 99%
“…To develop practical materials utilizing 10 B carriers, we previously designed, synthesized, and evaluated various BSH-containing organic compounds, which constitute a new class of tumor-seeking and water-soluble compounds, such as amino acids, peptides, etc. The in vitro evaluation of cytotoxicity, cell-killing effects, and micro-distribution analysis by immunocytochemical technique suggested that BSH-containing, tumor-seeking compounds might be potential lead compounds for developing novel B compounds for BNCT [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…An important requirement for compounds used for 10 B-NCT is a high selectivity of accumulation in tumor tissues and a high content of boron in molecules to create the required therapeutic concentration [3]. closo-Dodecaborate anion [B 12 H 12 ] 2attracts close attention of researchers when creating new agents for 10 B-NCT due to its low toxicity and high boron content [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Yield, 42%. (5). Derivative 4 (0.100 g, 0.2 mmol) was dissolved in acetonitrile (5 mL); concentrated hydrochloric acid (2 mL) was added dropwise, and the mixture was refluxed for 2 h. After cooling, the reaction mixture was extracted three times with 10 mL portions of dichloromethane.…”
Section: Introductionmentioning
confidence: 99%